The Role of Nurses in Improving Immunization Compliance Among Toddlers in Slum Areas - Anisa Putri; Aisyah Safitri (International Journal of Nursing and Midwifery Research, 2025)
Immunization is a crucial public health intervention for preventing vaccine-preventable diseases among toddlers; however, immunization compliance remains low in slum areas due to socioeconomic and health system barriers. Nurses, as frontline health workers, play a strategic role in promoting immunization within underserved communities. This study aims to examine the role of nurses in improving immunization compliance among toddlers in slum areas and to identify key challenges and enabling factors influencing immunization practices. This study employed a mixed-methods research design conducted in selected slum areas. Quantitative data were collected through structured questionnaires administered to parents or caregivers of toddlers to assess immunization compliance and related factors. Qualitative data were obtained through in-depth interviews and observations involving nurses engaged in community and maternal–child health services. Data analysis was performed using descriptive and inferential statistics for quantitative data and thematic analysis for qualitative data. The results indicate that nurses play a significant role in improving immunization compliance through health education, home visits, counseling and effective communication, reminder and follow-up systems, and community engagement. These interventions were found to enhance parents’ knowledge, attitudes, and trust toward immunization services. Key challenges identified include limited parental knowledge, socioeconomic constraints, high population mobility, and restricted access to health facilities. In conclusion, strengthening community-based nursing roles is essential for improving immunization compliance among toddlers in slum areas. Empowering nurses with adequate training, resources, and institutional support can enhance immunization coverage and contribute to better child health outcomes in vulnerable urban populations.